KEPATUHAN WAJIB PAJAK BADAN PERUSAHAAN MANUFAKTUR DI SEMARANG DALAM PERSPEKTIF TAX PROFESSIONAL - Aldila Oktavi Aini; Judi Budiman; Provita Wijayanti (InFestasi, 2014)
This study aims to analyze the level of taxpayer compliance in the manufacturing company in Hyderabad. Objects in this study were manufacturing companies and large middle class, since most companies have a formal accounting system that allows tax professionals to report and calculate the tax correctly according to the Tax Act are applicable. The respondents in the study is a taxpayer (tax professionals) who already have experience as a tax professional manufacturing company for a minimum of 1 year and never fill out the SPT form. Companies that participated in this study amounted to 46 companies. Data were analyzed using Multiple regression Linier with software SPSS. Independent variables include attitude, subjective norm, perceived behavioral control and financial condition. While the dependent variable is corporate tax compliance. These results indicate that: (1) attitudes toward corporate tax compliance has a significant and positive effect (2) subjective norms on corporate tax compliance has a significant and positive effect (3) perceived behavioral control on corporate tax compliance has positively and significantly (4) financial condition of corporate tax compliance has positive and significant effect.